Identification of Sandstone Reservoir Saturated by Oil Using Low Frequency Analysis with base on CWT and AVO Analysis - Sudarmaji S; Budi Eka Nurcahya (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Identification of sandstone resevoir saturated by oil has been conducted by mean low frequency and amplitude versus offset (AVO) analysis. Low Frequency analysis was has been conducted among 3D and 2D seismic data of PSTM gather using continuose wavelet transform (CWT) around 15hz. Low frequency analysis was done by calculating attribute gradient time frequency of instantaneous amplitude using continuous wavelet transform (CWT) around 15hz for detecting the existing diffusive wave from reflection seismic. Diffusive wave is a wave that appears due to fluid movement in porous rock, especially fluid of hydrocarbon with certain viscosity and permeability. While amplitude versus offset (AVO) analysis was done for detecting the impedance character of sandstone reservoir that related to porous rock. Amplitude versus offset (AVO) analysis was done by calculating gradient*intercept and observing the curve of wave reflectivity as a function of offset. The positive value of gradient*intercept and curve of reflectivity as a function of offset could be identified as AVOclass III and correlated to sandstone reservoir with low impedance and good porosity.